PENGARUH PERAMBATAN HUTAN TERHADAP ASPEK HIDROLOGI - hasbi arbi, hasbi hasbi (JURNAL LENTERA, 2012)
The purpose Water Resourse Depelopment used for controller and useful of water, where water controle used for to cotroling float water and normal volume, but water can be used for domestic water. Industtri, irigation, water tranfortation and water strength for run up electric mechines. To use of water shuld be have more water with the volume of water is relative counstan and sustainable, it can be happened if the support factor suck us porest and river can be protected and continue, so water resource can be enough and controlled. The forest is the best controle of rain water, until the rain water infilt into the ground can be more end runoff water is less, until porest can stop soil erosion. Ilegal forest couse the land / soil criyical condision end barren of land, until runoff water can be biggest and infitrasi will be less, finally ground water will be little, this couse at dryseasion river water will be less/dryness, until water river does not useful for sustainable. At wet seasion runoff water sweep away soil particle of soil erosion by rain to the rivers until the river base will be slope slightly, this be coused the rivers overflow, finally couse flood water , finally couse that soil pertility less, because the soil surfase erosion by rain water couse the porest bald and nonarable . this couse new plans can not grow again. This problem can be protected if local goverment implant forect and land conservation by reforestasion or planting new porest at the rigional place, finally misfortune ftoodwater and dryness can be preventatived.